Sistem Peradilan Pidana Anak Indonesia Berkaitan Penjatuhan Pidana Terhadap Anak - Dio Alberto Sirait; Mohamad Ismed (Universitas Jayabaya, 2021)
This research is intended to review “Criminal Imposition of Children in the Indonesian Child Criminal Justice System”. The imposition of a crime against a child will traumatize the child, and can have an impact on his life. Children should also be seen as a valuable asset of a nation and state in the future whose rights must be protected and protected. This is because after all in the hands of the children the progress of a nation will be determined. The more modern a country, the greater his attention in creating a conducive situation for developing children in the framework of protection. The research method is carried out in a normative juridical method based on positive law (dogmatics) to examine and review secondary data that refers to law or regulations with other applicable regulations. This research includes research on the actions of delinquency carried out by children is a manifestation of adolescent inflability without any intention of detrimental to others as shown in a crime that is listed in the Criminal Code (KUHP) where the perpetrators must be aware of the consequences and His actions and the perpetrators were able to be responsible for his actions. Thus, then, it is not right when the child’s delinquency is considered a pure crime.